(untitled) (Research, Society and Development, 2021)
In the actual times, with so many rehabilitation techniques and endodontic posts in the market, there are many doubts about which one is the best, the most cost-effective, the one that has more resistance among other questions. This work aimed to compare the intraradicular restorative treatments that involve the use of prefabricated posts and posts made with CAD-CAM, through a literature review in order to reinforce these procedures. Articles and other literary sources with interrelation to CAD-CAM and endodontic posts were surveyed through search in Pubmed, Scielo, Scopus, Lilacs and Google Scholar databases. The keywords: endodontic posts, CAD-CAM, prefabricated posts, customizable posts, fiberglass, carbon fiber were used. More than 100 articles were found, and after reading the abstract, 50 were selected. After reading, 26 were selected for the review. After reading, analyzing and interpreting the scientific studies, it was possible to verify that the CAD-CAM endodontic posts have satisfactory results, although there are few specific studies on them compared with the metallic cast posts and prefabricated posts.